K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 7 2015

Ta có: 5 - 3 = 2 ; 5+3 =8

=> 5+3 = 28

9-1 = 8 ; 9 +1 = 10

=> 9+1 = 810

..............

7 + 3 =

7-3 = 4 ; 7 +3 =10

=> 7 +3 = 410

18 tháng 11 2017

ngu thế 7+3=10

15 tháng 11 2021

bạ tự là đi minh mới lớp 6 nhá

undefined

15 tháng 10 2021

>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>>

27 tháng 9 2024

Bài 1:

a; \(\dfrac{7}{8}\) + \(x\) = \(\dfrac{4}{7}\)

     \(x\) = \(\dfrac{4}{7}\) - \(\dfrac{7}{8}\)

     \(x\) = \(\dfrac{32}{56}\) - \(\dfrac{49}{56}\)

     \(x=-\) \(\dfrac{49}{56}\)

Vậy \(x=-\dfrac{49}{56}\)

b; 6 - \(x\) = - \(\dfrac{3}{4}\)

         \(x\) = 6 + \(\dfrac{3}{4}\)

         \(x\) = \(\dfrac{24}{4}+\dfrac{3}{4}\)

         \(x=\dfrac{27}{4}\)

Vậy \(x=\dfrac{27}{4}\) 

c; \(\dfrac{1}{-5}\) + \(x\) = \(\dfrac{3}{4}\)

              \(x\) = \(\dfrac{3}{4}\) + \(\dfrac{1}{5}\)

              \(x=\dfrac{15}{20}\) + \(\dfrac{4}{20}\)

               \(x=\dfrac{19}{20}\)

Vậy \(x=\dfrac{19}{20}\) 

27 tháng 9 2024

      Bài 1:

d; - 6 - \(x\) = - \(\dfrac{3}{5}\)

      \(x\)   = - 6 + \(\dfrac{3}{5}\)

       \(x=-\dfrac{30}{5}\) + \(\dfrac{3}{5}\)

       \(x=-\dfrac{27}{5}\)

Vậy \(x=-\dfrac{27}{5}\)

e; - \(\dfrac{2}{6}\) + \(x\) = \(\dfrac{5}{7}\)

             \(x\) = \(\dfrac{5}{7}\) + \(\dfrac{2}{6}\)

             \(x\) = \(\dfrac{15}{21}\) + \(\dfrac{1}{3}\)

              \(x=\dfrac{15}{21}\) + \(\dfrac{7}{21}\)

               \(x=\dfrac{22}{21}\)

Vậy \(x=\dfrac{22}{21}\) 

f; - 8 - \(x\) =  - \(\dfrac{5}{3}\)

          \(x\) = \(-\dfrac{5}{3}\) + 8

         \(x\) = \(\dfrac{-5}{3}\) + \(\dfrac{24}{3}\)

         \(x\) = \(\dfrac{-19}{3}\)

Vậy \(x=-\dfrac{19}{3}\) 

 

            

 

2 tháng 9 2019

a.\(\frac{3}{5}+0,5-\frac{1}{4}+\frac{7}{2}\)/\(\frac{-6}{5}+\frac{1}{6}-\frac{13}{5}+0,5\)

=(\(\frac{3}{5}+\frac{1}{2}-\frac{1}{4}+\frac{7}{2}\)).60/(\(\frac{-6}{5}+\frac{1}{6}-\frac{13}{5}+\frac{1}{2}\)).60

=(36+30-15+210)/(-72+10-156+30)

=261/-188